The Behavioral Variant Frontotemporal Dementia Phenocopy Syndrome: A Review. (May 2021) - Power, Clodagh; Lawlor, Brian A.
Objectives: The relatively recent identification of a subgroup of patients with apparent behavioral variant frontotemporal dementia (bvFTD) that fails to progress with time has led to a reevaluation of our understanding of bvFTD, and a growing body of research that attempts to characterize the mimic or "phenocopy" syndrome. In this article, we review the literature relating to the phenocopy syndrome, focusing in particular on distinguishing characteristics and potential etiologies. Methods: Published articles were identified via a systematic search of PubMed and Embase. Observational and interventional studies, case reports, and case series were sought for inclusion. Results: While bvFTD and the phenocopy syndrome are clinically indistinguishable at initial presentation, the presence or absence of characteristic changes on neuroimaging predicts 2 very different illness trajectories. The etiology for the phenocopy presentation remains uncertain. It is likely that the syndrome represents a heterogenous assortment of clinical frontal syndromes encompassing atypical neurodegenerative, psychiatric, psychological, and as yet unknown neuropsychiatric causes. Conclusions: Although the prognosis of the phenocopy syndrome is generally held to be more favorable than that of bvFTD, patients and families are subject to major disruption in their relationships and social and occupational functioning. Early recognition is crucial to facilitate timely interventions aimed at maintaining relationships, roles, and quality of life of those affected.